Planning the future physicians and nurses in Portugal - Lopes, Diana Fernandes; Dias, Ana; Simões, Jorge; Castro, Eduardo Anselmo (Conferência - Investigação e Intervenção em Recursos Humanos, 2019)
Human health resources (HHR) are the keystone of any health system, by delivering health services to the population. According to the WHO, a shortage of the health workforce (physicians and nurses) in the future is expected. On the one hand, ageing populations will need more and different healthcare; on the other hand, the physician’s age average in Europe is increasing. The perspective of the sudden retirement of large groups of professionals in a short time is a main problem to address. Moreover, the training of a physician is a long process, which makes it impossible to cover the needs of those health professionals at short notice. Furthermore, there are health workforce imbalances that should be addressed. On the one hand, the nurse to physician ratio varies significantly across European countries, from below one nurse to every physician in Greece to between four and five per physician in Denmark and Finland (OECD, 2017). The Portuguese ratio, 1.5, is below the European Region average (2.2) and the OECD average (2.8) (OECD, 2017). On the other hand, the proportion of general practitioners among all physicians should be increased, in order to strengthen primary health care (this ratio varies from 0.5 in France to 0.13 in Portugal; 0.2 is the European Region average). The complexity of this topic is highlighted by the WHO, with the process of planning, regulating and managing the HHR being recognized as the heart of the Health 2020 policy. The planning process aims to streamline decision-making to ensure that the right number of HHR is available in the right time and in the right places to meet the population’s needs and to guarantee their equitable access to healthcare as well as high quality services.